2005
DOI: 10.1682/jrrd.2005.03.0054
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of multidisciplinary treatment program on long-term outcomes of individuals with Parkinsons disease

Abstract: Abstract-We examined the impact of multidisciplinary clinical management of the Parkinson's Disease Research, Education, and Clinical Center program on Parkinson's disease progression. Initial and follow-up scores on the Part III Motor Examination subscale of the Unified Parkinson's Disease Rating Scale (UPDRS) were examined. Overall, 37 (75.5%) of the 49 patients demonstrated stable or improved UPDRS motor scores at 1-to 3-year follow-up; in the 1-year group (n = 28), 22 patients (78.6%) improved, while 6 (21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 30 publications
0
35
0
1
Order By: Relevance
“…The caregivers (N = 49) of all consecutive subjects referred with a movement disorder and seen for an initial or follow-up neuropsychological screening from [19]. We obtained approval for this study from the local VAMC institutional review board.…”
Section: Methodsmentioning
confidence: 99%
“…The caregivers (N = 49) of all consecutive subjects referred with a movement disorder and seen for an initial or follow-up neuropsychological screening from [19]. We obtained approval for this study from the local VAMC institutional review board.…”
Section: Methodsmentioning
confidence: 99%
“…11 There are several studies of multidisciplinary care in Parkinson's disease comparing outcomes before and after the intervention. Outpatient multidisciplinary care programmes have reported shortterm improvements in UPDRS motor score, 12 gait speed and stride length, [13][14] speech, depression and health-related quality of life. 13 low up) have also been reported, and the authors comment that close multidisciplinar y working was key to success.…”
Section: Effectiveness Of Multidisciplinary Carementioning
confidence: 99%
“…13 low up) have also been reported, and the authors comment that close multidisciplinar y working was key to success. 15 Inpatient multidisciplinar y rehabilitation for Parkinson's disease has also been reported to be effective in studies using a trial design comparing pre-and postintervention outcomes. Using the Nottingham Health Profile (a measure of health-related quality of life), Sitzia et al found improvements in 'pain', 'emotional reactions' and 'physical mobility' and in overall quality of life.…”
Section: Effectiveness Of Multidisciplinary Carementioning
confidence: 99%
See 1 more Smart Citation
“…In Germany, a Parkinson network has led to a greatly improved interaction and communication between the movement disorders specialists and the general neurologists, enabling more efficient initiation of advanced therapies. Also intensive multidisciplinary rehabilitation interventions for people with PD have been shown particularly effective at improving quality of life and motor function [11][12][13].…”
mentioning
confidence: 99%